Independent segregation of the two arms of the Escherichia coli ori region requires neither RNA synthesis nor MreB dynamics. - Wang, X; Sherratt, D (2010)
The mechanism of Escherichia coli chromosome segregation remains elusive. We present results on the simultaneous tracking of segregation of multiple loci in the ori region of the chromosome in cells growing under conditions in which a single round of replication is initiated and completed in the same generation. Loci segregated as expected for progressive replication-segregation from oriC, with markers placed symmetrically on either side of oriC segregating to opposite cell halves at the same time, showing that sister locus cohesion in the origin region is local rather than extensive. We were unable to observe any influence on segregation of the proposed centromeric site, migS, or indeed any other potential cis-acting element on either replication arm (replichore) in the AB1157 genetic background. Site-specific inhibition of replication close to oriC on one replichore did not prevent segregation of loci on the other replichore. Inhibition of RNA synthesis and inhibition of the dynamic polymerization of the actin homolog MreB did not affect ori and bulk chromosome segregation.